THE ROLE OF SMM MARKETING IN SMALL BUSINESS DEVELOPMENT DURING A PANDEMIC - U. Djamolova; N. Azzamova (TADQIQOTLAR.UZ, 2024)
Abstract: In small business development during a pandemic, SMM creates the basis for positive economic growth through the use of marketing and improves the quality of products and services while reducing costs.